STUDI KASUS LABORATORIUM PENDIDIKAN AGAMA ISLAM DI SMAN 3 BANDUNG - Achmad Dudin (Badan Litbang dan Diklat Kementerian Agama RI, 2018)
AbstractIslamic Religious Education (Pendidikan Agama Islam/PAI) is provided by following the guidance that religion shall be taught to human beings with a vision of manifesting pious people who only afraid of Allah SWT and have noble morality, and aims to produce people who are honest, fair, virtuous, ethical, respectful, disciplined, harmonious and productive, both personally and socially. The demands of such vision promote the development of PAI laboratory in accordance with the relevant education level. This study aims to evaluate the PAI laboratory at schools from the point of view of standard level, utilization, assessment of learners and determinants of PAI laboratory management. The method deployed in this research is qualitative evaluative through a case study carried out at SMAN 3 Bandung commenced as of July until December 2016. The research findings indicate that the PAI laboratory of SMAN 3 Bandung has reached an adequate level of standard and utilization in the management of the said PAI laboratory. This can be understood by the existence of positive assessment by the students and some supports delivered for management factors of the PAI laboratory of SMAN 3 Bandung. Furthermore, in this study, it is recommended the need of maintaining and improving the level of standard, utilization, and supporting factors of PAI laboratory management, in order for it to function effectively and optimally.Â AbstrakPendidikan Agama Islam (PAI) diberikan dengan mengikuti tuntunan bahwa agama diajarkan kepada manusia dengan visi untuk mewujudkan manusia yang bertakwa kepada Allah SWT dan berakhlak mulia, serta bertujuan untuk menghasilkan manusia yang jujur, adil, berbudi pekerti, etis, saling menghargai, disiplin, harmonis dan produktif, baik personal maupun sosial. Tuntutan visi ini mendorong dikembangkannya laboratorium PAI sesuai dengan jenjang pendidikan. Penelitian ini bertujuan untuk mengevaluasi laboratorium PAI di sekolah dilihat dari tingkat standar, pemanfaatan, penilaian peserta didik dan faktor penentu pengelolaan laboratorium PAI. Metode dalam penelitian ini adalah kualitatif evaluatif, dengan studi kasus di SMAN 3 Bandung pada bulan Juli hingga Desember 2016. Hasil penelitian menunjukkan bahwa laboratorium PAI SMAN 3 Bandung telah mencapai tingkat standar, dan pemanfaatan yang memadai dalam pengelolaan laboratorium PAI. Hal itu dapat di pahami dengan adanya penilaian yang positif dari siswa dan dukungan terhadap faktor pengelolaan laboratorium PAI SMAN 3 Bandung. Selanjutnya dalam penelitian ini direkomendasikan perlunya mempertahankan dan meningkatkan tingkat standar, pemanfaatan, dan faktor pendukung pengelolaan laboratorium PAI, agar fungsinya efektif dan lebih maksimal.